The feasibility and acceptability of mood on track: an online psychological intervention for bipolar disorder - Elizabeth Newton; Gurvir Matharu; Christopher A. Jones; Arielle Kaufman; Radha Yagnik; Sarona McDonald; Jessica Makepeace; Melissa Dwyer; Alex Copello (International Journal of Bipolar Disorders)
Abstract Background Despite evidence that psychological interventions improve recovery for bipolar disorder, access to these in the United Kingdom is limited; online delivery provides opportunities to increase this. Mood on Track is a psychological therapy programme for bipolar disorder combining a Cognitive Behavioural Therapy group intervention with individual relapse prevention. The present study reports on a feasibility and acceptability trial of Mood on Track online, implemented within a routine clinical service, in preparation for a Randomised Controlled Trial. The online version retains the therapeutic elements of the face-to-face intervention, but is delivered via Zoom over more sessions and includes online exercises and breakout rooms. Method A within-groups non-randomised longitudinal interventional study of feasibility and acceptability. Participants completed psychometric questionnaires at four time points from baseline to six months post-group intervention to evaluate change in recovery. Feasibility and acceptability of the intervention and a future study were assessed by measuring recruitment, intervention attendance and outcome measure completion. Results Rates of recruitment, intervention completion and outcome measure completion demonstrate that Mood on Track online and a larger future trial are feasible and acceptable. Analysis of efficacy found that the primary outcome measure of personal recovery on the Bipolar Recovery Questionnaire significantly increased between the start and end of the group intervention and continued to significantly increase at follow-up. Scores on the secondary outcome measure of the Generalised Anxiety Disorder-7 questionnaire decreased significantly between the start and end of the group intervention. Conclusions The present study provides quantitative evidence that a future RCT of Mood on Track online is feasible in terms of recruitment, delivery procedures and data collection. The findings provide promising evidence that Mood on Track online is an acceptable intervention to service users and shows signs of efficacy through significantly increased recovery and reduced anxiety. This adds to literature demonstrating that online psychological interventions are effective and provide an innovative method for delivery. Provision of digital therapies could increase offer and take-up of therapy for people with bipolar disorder and improve recovery.